A Birth Cohort Analysis to Study Dog Walking in Adolescence Shows No Relationship with Objectively Measured Physical Activity - Westgarth, Carri; Ness, Andrew R.; Mattocks, Calum; Christley, Robert M. (Frontiers in Veterinary Science, 2017)
Physical inactivity during childhood and adolescence is a serious health concern. There are few studies of the activity undertaken by adolescents when walking with the family dog, and the effect of this on objectively measured physical activity levels. Objective measures of physical activity using accelerometers were recorded at age 11-12 years, 13-14 and 15-16 years in the Avon Longitudinal Study of Parents and Children (ALSPAC, UK) birth cohort during the 2000s. Family pet ownership was collected retrospectively using a questionnaire at age 18, for the ages 7, 11, 13 and 15 years. In addition approximate frequency per week of walks undertaken with dogs were also reported. Multi-level multivariable modelling was used to investigate the relationship between dog ownership and dog walking status, and physical activity outcomes. There were a total of 4,373 complete data observations for use in 2,055 children. Reported participation in dog walking tended to increase during adolescence, as did dog ownership. The majority of adolescents that own dogs reported walking them either 2-6 times per week (range 39-46%) or never (range 27-37%). A small minority (7-8%) reported walking with their dog every day. Most reported never walking any other dog either (94-87%). We found no evidence for an association between dog ownership or reported dog walking, and objectively measured physical activity (counts per minute, P=0.3), or minutes of moderate-to-vigorous physical activity, P=0.7) during adolescence. This study provides no evidence to support a relationship between adolescent dog ownership and physical activity, and demonstrates the importance of using objective activity measures and considering dog walking rather than just dog ownership.